Neuroimmune cardiovascular interfaces in atherosclerosis - Mohanta, Sarajo K.; Yin, Changjun; Weber, Christian; Habenicht, Andreas J. R. (Frontiers in Cell and Developmental Biology, 2023)
Two pairs of biological systems acting over long distances have recently been defined as major participants in the regulation of physiological and pathological tissue reactions: (i) the nervous and vascular systems form various blood-brain barriers and control axon growth and angiogenesis; and (ii) the nervous and immune systems emerge as key players to direct immune responses and maintain blood vessel integrity. The two pairs have been explored by investigators in relatively independent research areas giving rise to the concepts of the rapidly expanding topics of the neurovascular link and neuroimmunology, respectively. Our recent studies on atherosclerosis led us to consider a more inclusive approach by conceptualizing and combining principles of the neurovascular link and neuroimmunology: we propose that the nervous system, the immune system and the cardiovascular system undergo complex crosstalks in tripartite rather than bipartite interactions to form neuroimmune cardiovascular interfaces (NICIs).